Effectiveness of 2009 pandemic influenza A(H1N1) vaccines: a systematic review and meta-analysis - Lansbury, Louise E.; Smith, Sherie; Beyer, Walter; Karamehic, Emina; Pasic-Juhas, Eva; Sikira, Hana; Mateus, Ana; Oshitani, Hitoshi; Zhao, Hongxin; Beck, Charles, R; Nguyen-Van-Tam, Jonathan (Elsevier, 2017)
Background: The clinical effectiveness of monovalent influenza A(H1N1)pdm09 vaccines has not been comprehensively summarised. We undertook a systematic review and meta-analysis to assess vaccine effectiveness (VE) for adjuvanted and unadjuvanted vaccines.